Ethnobotany of Societies Tanjung Belit, Muara Bio and Batu Sanggan Around the Wild Reserve Bukit Rimbang Bukit Baling Riau, Pekanbaru Indonesia - Ikhsan Matondang; Sri Endarti Rahayu; Ritchi Y.H.L.T (Journal of Tropical Biodiversity, 2022)
Villagers around the wildlife reserve Bukit Rimbang Bukit Baling Riau are societies that still used the wealth of plant resources for daily living. Tanjung Belit, Muara Bio and Batu Sanggan are villages around wild reserve Bukit Rimbang Bukit Baling, Riau. The tribes that inhabit these three villages are Domo, Melayu, Tonga, and Kafe tribes. Not much scientific information reveals the use of plants by the societies in the three villages mentioned above. The purpose of this study is to inventory the use of plants in the three villages mentioned. The study was conducted in April 2016 by interviewing societies leaders and people with knowledge about the use of plants for the daily use of the societies and direct observations during field trips. The results obtained 95 species of plants in 49 family are used by the societies in everyday use in the three villages. The use of the plant by the three societies villagers 55 species for medicine, 39 species for food, 8 species for board material, 5 species for industrial material, 2 species for ornamental, 1 species for aphrodisiac, and 2 for others. This knowledge is very important for the next generations and also as a guide for the existence of the used to be preserved sustainability.